Multimodal ayurvedic approach in the management of type 2 diabetes mellitus in insulin therapy: a case report (Indian Journal of Case Reports, 2021)
In the literature of Ayurveda, Prameha (diabetes mellitus [DM]) is a disease where derangement is seen in urine with respect to its quantity and quality. The basic pathology involved in the disease is the Bahu, Abaddha Medas, and Kleda. Prameha can be well correlated to DM with respect to its pathology and symptoms. Here, we present the case of a 44-year-old male who came with complaints of restlessness, generalized weakness, giddiness, and pain in bilateral calf muscles for the past 4 months. Based on Ayurvedic examinations, he was diagnosed to have Margavarnajnya Madhumeha ( obese diabetic), suitable food, lifestyle, and medications were advised after assessing Prakriti, Dosha, etc. By Ayurvedic therapy, considerable improvement was seen in the quality of life. The case was followed up for 4 years and the patient’s condition was maintained well throughout, without any complications. This article reports a case of Type 2 DM on insulin therapy which was completely managed by Ayurvedic therapeutic modalities and all the oral hypoglycemic drugs along with insulin were withdrawn gradually during the course of the treatment.